Sosialisasi Model Pembelajaran Berbasis Literasi Digital di Sekolah Dasar - Irmaningrum, Rizka Novi; Humairah, Humairah; Halisah, Aulina; Nisa, Zahrotun (Universitas Pahlawan Tuanku Tambusai, 2024)
This community service outreach was carried out because there were many teachers who had not implemented the learning model expected in the Merdeka curriculum. The aim of this socialization is to produce quality teaching for teachers by socializing digital literacy-based learning models in the independent curriculum at SD Muhammadiyah 1 Sidoharjo. This socialization activity can provide knowledge to improve the quality of teaching in the independent curriculum. The method that will be used is the socialization planning stage for grade 1, 2, 4 and 5 teachers by preparing an analysis of the Merdeka curriculum. The second stage is the implementation of the socialization of digital literacy-based learning models. The third stage is evaluation and follow-up to differentiate the results of the pretest and posttest. The results of the community service that has been carried out, namely the successful implementation of community service activities with the above components, can also be seen from the satisfaction of the participants after participating in the socialization. Summary of the implementation of community service activities that have been carried out well and teachers are able to apply digital literacy-based learning models.